1993
DOI: 10.1093/oxfordjournals.humrep.a137950
|View full text |Cite
|
Sign up to set email alerts
|

Andrology: Mitochondrial disease and reduced sperm motility

Abstract: Mitochondrial dysfunction reduces aerobic energy production and results in symptoms from various tissues, depending on metabolic demands. Mitochondrial adenosine triphosphate (ATP) is essential for sperm motility. Sperm motility was investigated in a patient with a mitochondrial disease caused by reduced activity of the mitochondrial enzyme complexes I and IV, and in two control subjects. Spermatozoa were cultured in media containing various energy substrates. Motility was judged by light microscopy, and ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
97
0
11

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(112 citation statements)
references
References 0 publications
4
97
0
11
Order By: Relevance
“…A s t h e n o z o o s p e r m i a o r oligoasthenozoospermia has been reported previously in patients suffering from typical mtDNA diseases [123,124]. Other studies have shown a correlation between the quality of the sperm and the functionality of the respiratory chain in sperm mitochondria [125].…”
Section: The Usp26 Gene Mutationsmentioning
confidence: 80%
“…A s t h e n o z o o s p e r m i a o r oligoasthenozoospermia has been reported previously in patients suffering from typical mtDNA diseases [123,124]. Other studies have shown a correlation between the quality of the sperm and the functionality of the respiratory chain in sperm mitochondria [125].…”
Section: The Usp26 Gene Mutationsmentioning
confidence: 80%
“…If the mitochondria are dysfunctional they may be incapable of providing sufficient ATP for optimal motility (Folgero et al, 1993). In this study we probed the mitochondrial genome in the region located between the D loop and Cox II gene.…”
Section: Discussionmentioning
confidence: 99%
“…Magnification, ϫ13,000). motility by yet unknown mechanisms (40,41). One simple explanation may be insufficient energy production to sustain forward motility and cell volume regulation.…”
Section: Figmentioning
confidence: 99%